(untitled) (Italian Journal of Public Health, 2011)
Soil is an excellent source of unknown microorganisms since bacteria, algae, protozoans, yeasts, moulds, and microscopic worms are routinely found in this environment. Therefore, soil is a medium in which life is sustained in a fragile biological balance. Bacteria play an important role in nutritional chains that are an important part of biological balance. In the present study, four different soil samples were collected from the rhizosphere of i) Sapota zapotilla, ii) Eucalyptus species, iii) Ficus religiosa from Lahore and iv) soil from Changa manga, Pakistan. A Total of 28 bacterial species were isolated and classified in the period between November 2008 and December 2009. All species were cultured on recommended media for verification of biochemical characteristics. The results showed that at least fifteen Gram-positive bacterial species were present in samples and these were considered as the major group constituting the bacterial population strains.